Lower risk of musculoskeletal pain among patients with end-stage renal disease treated by hemodialysis: A frequency-matched retrospective cohort study. Issue 33 (August 2018) - Wang, Jie-Sian; Chiang, Jen-Huai; Hsu, Heng-Jung
Abstract : Abstract: Musculoskeletal pain is experienced by 5%–14% of the general adult population, and it is highly common among patients with chronic kidney disease (CKD). Therefore, the purpose of the study was to decide the prevalent rate of musculoskeletal pain in end-stage renal disease (ESRD) patients and to analyze this relationship between myalgia and ESRD using clinical features and determinants. A total of 93, 013 patients who received ESRD diagnoses during 2000 and 2010 and were followed up until December 31, 2011, were identified from the Longitudinal Health Insurance Database 2000 (LHID2000) of the National Health Research Institutes (NHRI); non-ESRD controls were also selected from the LHID2000. The results indicated that the risk of chronic musculoskeletal pain is significantly lower in the hemodialysis treated ESRD cohort (subhazard ratio = 0.52, P < .0001), despite of sex, age, or comorbidities. Older patients were discovered to be at lower risk of chronic musculoskeletal pain (subhazard ratio = 0.94, P = .0765), with those aged 40 to 64 years having the highest hazard ratios (subhazard ratio = 1.21, P < .0001), and the prevalence of chronic musculoskeletal pain in women was higher than that in men (vs female sex; subhazard ratio = 0.69, P < .0001). Kaplan–Meier analysis revealed a higher cumulative incidence of myalgia development in the non-ESRD cohort compared with the ESRD cohort (log-rank test, P < .001). Clinicians should assess the risk of chronic musculoskeletal pain in such patients and provide appropriate and timely support of hemodialysis. Abstract : Supplemental Digital Content is available in the text